ANALYSIS OF THE GRAMMATICAL SIGNIFICANCE OF THE TRANSPOSITION USED IN THE NOVEL "NIGHT AND DAY" BY ABDULHAMID CHOLPON, A REPRESENTATIVE OF THE 20TH CENTURY LITERATURE - Kabilova Sayyora Abdukarimova; Rahmatullayeva Fatima Tahirjon kizi (Western European Studies, 2024)
The novel “Day and Night” occupies a special place in the history of Uzbek literature and is considered the first dialogue novel. Unfortunately, the “Kunduz” section is unfinished. It is considered one of the works reflecting the spiritual peace of the people of that time and the policies of Tsarist Russia in our country
Keywords: Night and day; period; metaphor